The Role of Customer Satisfaction in Mediating The Influence of Customer Experience on Customer Loyalty for Beauty Products - Lestari, Lusya; Hermawan, Adam; Prehanto, Adi (Journal of Investment Development, Economics and Accounting, 2025)
This study aims to determine the influence of customer experience on customer loyalty, with customer satisfaction serving as a mediator, specifically for beauty products on the Shopee platform. Employing a quantitative approach, this associative research explores causal relationships and was conducted with 140 respondents who are customers of beauty products on Shopee. The findings indicate that customer satisfaction mediates the relationship between customer experience and customer loyalty. Additionally, both customer experience and customer satisfaction have a direct impact on customer loyalty, while customer experience also influences customer satisfaction. Given the popularity of beauty products and the significance of e-commerce in today’s society, investigating customer experiences with beauty products on the Shopee platform offers valuable insights into this evolving sector.